The Model of Competency for School Administrators under the Yala Primary Educational Service Area Office 2 - Datoomada, Nurhayatee; Kao-ian , Jarunee; Suwanno , Phimpawee (Al-HIKMAH Journal, 2024)
The objectives of this research were to 1) study the condition and model of competency for school administrators under the Yala Primary Educational Service Area Office 2, and 2) create the model of competency for school administrators under the Yala Primary Educational Service Area Office 2. The research process involved two steps. Step 1: examining the condition and model related to competency for school administrators to gain points for interview and collect qualitative data collection with 11 participants by semi-structured interviews with 11 participants were processed. The data was analyzed by employing content analysis to create a conceptual framework and outline the draft model of competency for school administrators. Step 2: creating the draft model of competency for school administrators and submitting to three experts for validation and content validity were proceeded. The index of item objective congruence (IOC) of three experts ranged from 0.67 to 1.00 with a confidence level of .94 and applied the model of competency for school administrators to 315 samples. The data analysis was conducted by using statistical software package to calculate means and standard deviations. The results showed that: 1. The condition and model of competency for school administrators under the Yala Primary Educational Service Area Office 2 comprised six components which were 1) achievement-oriented management, 2) teamwork, 3) critical thinking, 4) motivation, 5) developing relationships among people in the organization, and 6) leadership. 2. The model of competency for school administrators under the Yala Primary Educational Service Area Office 2 consisted of six components involving Component 1: achievement-oriented management included 1) school administrators planned for school improvement, 2) school administrators used technology in various aspects of management, and 3) school administrators managed the school economically, efficiently, and effectively. Component 2: teamwork consisted of 1) school administrators were as good role models and followers who accepted others’ opinions, 2) school administrators dedicated to work and continuously developed oneself, and 3) school administrators appreciated colleagues and accepted the majority’s voice. Component 3: critical thinking consisted of 1) school administrators organized meeting for planning and developing systematic strategies to address solutions, 2) school administrators proposed options and problem prevention strategies, and 3) school administrators introduced innovative ideas for vision development. Component 4: motivation included 1) school administrators praised and honored teachers and staff, 2) school administrators provided opportunities for teachers and staff to fully utilize their abilities, and 3) school administrators held to democratic principles in their work. Component 5: developing relationships among people in the organization included 1) school administrators promoted and facilitated convenience for teachers and staff, 2) school administrators supported teachers and staff in self-development, and 3) school administrators continually adjusted work practices for teachers and staff. Component 6: leadership included 1) school administrators showed modernism, 2) school administrators were ethical and disciplined persons being as good role models, and 3) school administrators encouraged and inspired teachers and staff to realize and accept changes. When finding for the appropriateness of implementation, it was found that the overall and individual components were at a high level.